Relativity and the Dimensionality of the World - Petkov, Vesselin; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
All physicists would agree that one of the most fundamental problems of the 21st century physics is the dimensionality of the world. In the four-dimensional world of Minkowski (or Minkowski spacetime) the most challenging problem is the nature of the temporal dimension. In Minkowski spacetime it is merely one of the four dimensions, which means that it is entirely given like the other three spacial dimensions. If the temporal dimension were not given in its entirety and only one constantly changing moment of it existed, Minkowski spacetime would be reduced to the ordinary three-dimensional space. But if the physical world, represented by Minkowski spacetime, is indeed four-dimensional with time being the fourth dimension, then such a world is drastically different from its image based on our perceptions. Minkowski four-dimensional world is a block Universe, a frozen world in which nothing happens since all moments of time are given 'at once', which means that physical bodies are four-dimensional worldtubes containing the whole histories in time of the three-dimensional bodies of our everyday experience. The implications of a real Minkowski world for physics itself and especially for our world view are enormous. The main focus of this volume is the question: is spacetime nothing more than a mathematical space (which describes the evolution in time of the ordinary three-dimensional world) or is it a mathematical model of a real four-dimensional world with time entirely given as the fourth dimension? It contains fourteen invited papers which either directly address the main question of the nature of spacetime or explore issues related to it. Audience Physicists and philosophers
The Meaning of Dimensions -- Some Remarks on the Space-Time of Newton and Einstein -- The Adventures of Space-Time -- Physics in the Real Universe: Time and Space-Time -- The Real World and Space-Time -- Four-dimensional Reality and Determinism; an Answer to Stein -- Relativity, Dimensionality, and Existence -- Canonical Relativity and the Dimensionality of the World -- Relativity Theory Does Not Imply that the Future Already Exists: A Counterexample -- Absolute Being versus Relative Becoming -- An Argument for 4D Block World from a Geometric Interpretation of Nonrelativistic Quantum Mechanics -- Space-time: Arena or Reality? -- Dynamical Emergence of Instantaneous 3-Spaces in a Class of Models of General Relativity -- Lorentzian Space-Times from Parabolic and Elliptic Systems of PDEs.
Keywords: PHYSICS; SCIENCE -- PHILOSOPHY; PHYSICS; HISTORY AND PHILOSOPHICAL FOUNDATIONS OF PHYSICS; PHILOSOPHY OF SCIENCE; CLASSICAL AND QUANTUM GRAVITATION, RELATIVITY THEORY